Relationship between Career Intention and Academic Performance of University Students: A Study Based on Khulna Region, Bangladesh - Amanta Hasnat Oyshi; Samia Shanjabin; Kazi Snigdha Yasmin (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2022)
Every student in their academic life faces dilemmas regarding their career choice and academic performance plays a big role here. This present study seeks to investigate the relationship between career intention and academic performance of University students. Along with these, the study also aims to examine the relationships among multiple demographic variables of University students. Moreover, a self-administered questionnaire survey was conducted to collect data from the participants. Altogether a hundred students studying at different universities participated in the survey. The hypothesis of this study is entitled to determine the relationship between career intention regarding “Entrepreneurship” and “Academic performance”. This study also determines the relationship between career intention regarding “Corporate job” and “Academic performance”. However, correlation and linear regression analysis were employed to test the research hypothesis. The analysis of cross-tabulation has been conducted to represent the relationship between demographic characteristics and the academic performance of the respondents. The study findings reveal that there is a very weak relationship between entrepreneurial mindset and academic performance. Hence, this study also clarifies that there is a strong relationship between a job-oriented mindset and academic performance. The findings of this research provide a better understanding to the policymakers of universities about developing the curriculum such that the university students can be benefitted while setting their career goals and these will be beneficial for the society as a whole. Keywords: Academic performance, students, career intention, entrepreneurship, job.